Conflict resolution : actors, dynamics, and cases - Carvalho Oliveira, Gilberto; Sousa, Ricardo Real P. (Peace and conflict studies, 2021)
"Conflict Resolution - Actors, Dynamics and Cases deals with multiple concepts and themes of the broad subject area of conflict resolution, seeking to highlight empirical studies that examine several topics from conflict prevention to peacebuilding, including conflict management, institution building, the role of formal and informal actors, the features of conflicts in different political contexts and the methods and strategies used for resolution or transformation (mediation, non-violence, reconciliation, transitional justice, second track diplomacy, peace education, post-conflict reconstruction, among others) in intra- and inter-state conflicts. The book is open to several methodological approaches, focusing on empirical studies that address several cases, including studies on Cyprus, the South Caucasus region, DR Congo, the Middle East region, Tunisia and Iraq, as well as on the role of regional organizations such as the European Union in peace-making and peacebuilding. Conceived this way, this edited volume on conflict resolution complements existing books on the theme, seeking not only to apply conflict resolution's theoretical frameworks and concepts to contemporary case studies but also to contribute, based on these empirical studies, to advance the academic debate towards critical perspectives that guide the conflict resolution field to more pluralist, emancipatory and transformative approaches"--